Inclusion Around the Globe - Szabados, Péter (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Gertz, S. K., Huang, B. & Cyr. L. (Eds.) (2018): Diversity and Inclusion in Higher Education and Societal Contexts, Palgrave Macmillan, New York.